INTEGRATING EIL PEDAGOGY IN A PRE-SERVICE ï¿¼ï¿¼TEACHER EDUCATION PROGRAM - Nugrahenny T. Zacharias (TEFLIN, 2014)
Among the existing pedagogies to teach English, many scholars have claimed that English as International Language (EIL) pedagogy is the most suitable pedagogy to the changing sociolinguistic landscape of English and English users. Despite such strong claims, little is actually known on how EIL pedagogy is experienced by teachers. The present article documented the experience of ten bilingual English student-teachers (BESTs) on practicing EIL pedagogy in a Microteaching course and during the teaching practice. Data were collected primarily from a focus group discussion and three individual interviews. The findings of the study indicated the complexity of practicing EIL pedagogy in the classroom. BESTs were enthusiastic about EIL pedagogy that they voluntarily decided to continue practicing the pedagogy during the teaching practice. Despite the enthusiasm in practicing EIL, the study points to the limited understanding BESTs have of EIL pedagogy when it relates to setting pedagogic models. Although some BESTs did attempt to bring local Englishes into the classroom, it seems they continue to perceive Native English Speakers (NES)/standard English as the desirable pedagogical models. The paper ends with specific suggestions for pre-service teacher education program to better prepare BESTs to teach English in the era of World English particularly in Expanding circle countries.Â